Pengaruh Adaptabilitas Karier dan Motivasi Intrinsik terhadap Kesiapan Kerja Generasi Z di Kabupaten Tasikmalaya - Eka Nurazizah; Raisa Hilia Aini Syifa (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study examines the influence of career adaptability and intrinsic motivation on the work readiness of Generation Z in Tasikmalaya Regency. The research is motivated by high unemployment rates and the rising phenomenon of youth in the NEET category, indicating low post-pandemic workplace preparedness. Employing a quantitative survey method, data were gathered from 100 Gen Z respondents (aged 16–31) using Likert-scale questionnaires through purposive sampling, and subsequently analyzed via multiple linear regression using SPSS 31.The partial test results indicate that career adaptability has a positive and significant effect on work readiness (t = 3.984; p = 0.000), as does intrinsic motivation (t = 4.751; p = 0.000$). Simultaneously, both variables significantly impact work readiness (F = 122.363; p = 0.000). The coefficient of determination demonstrates that these two factors contribute 71.6% to work readiness, while the remaining 28.4% stems from external variables. This research concludes that strengthening internal motivation and adaptive capacity is crucial for Gen Z's competitiveness, thereby requiring intensive attention from the local government, academic sector, and all relevant institutions located in the region.